OCTOBER 21 IS THE DAY WHEN THE UZBEKI LANGUAGE WAS GRANTED THE STATE LANGUAGE STATUS (International journal of artificial intelligence, 2025)
October 21 is an important date in the Republic of Uzbekistan, marking the day when the Uzbek language was granted the status of the state language. On October 21, 1989, the Supreme Soviet of the Uzbek SSR adopted the decision “On Granting the Uzbek Language the Status of the State Language in the Uzbek SSR.” This decision strengthened the official legal status of the Uzbek language and regulated its use in all spheres of state and social life. As a result, the Uzbek language began to be used as the primary language in government institutions, education, culture, and mass media. This date is celebrated as a significant step towards the development of the national language and culture, as well as the formation of an independent Uzbekistan.